The Paradox of Inter/Disciplinarity: A Rethinking of the Politics of Inter/Disciplinarity and ‘Women’s and Gender Studies’ for the Current Moment - McCallum, Karen; Rahaman, Felicia; Turnbull, Haley (Atlantis)

(untitled) (Mount Saint Vincent University, 2015)
In this paper, we argue that Women’s and Gender Studies (WGS) should be embraced and acknowledged as a discipline. This is premised on two contentions: that disciplines are arbitrarily differentiated and that couching WGS in the mystique of interdisciplinarity serves to marginalize the study of issues pertinent to gender, women, and feminisms in comparison to other topics. We maintain that WGS is disciplinary, but we also highlight the importance of multi- and interdisciplinary partnerships and research.